Quality of Human Resources via Accountant’s Intellectual Competence in Multinational Enterprises in Hanoi, Vietnam - Duc Tai Do; Quynh Anh Doan Thi; Duc Dinh Truong; Trung Thanh Le (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
This study was conducted to evaluate the quality of human resources via accountant’s intellectual competence in multinational enterprises in Hanoi, Vietnam. Based on a literature review and interviews, the dependent variable of the quality of human resources in this study includes four attributes literacy level, understanding of specialized knowledge, professional skills, and working experience. As a descriptive analysis, this study used Cronbach's Alpha, Independent T-test, and ANOVA for measuring the quality of human resources via accountant’s intellectual competence. The results of the study show that the quality of human resources via accountant’s intellectual competence achieved an average of 4.027 with Cronbach's Alpha coefficient greater than 0.6. This indicates that the quality of human resources via accountant’s intellectual competence of men and women is not different; there are no differences in evaluating the quality of human resources between chief accountants, general accountants and accountants. Based on these findings, some recommendations are given to improve the quality of human resources via accountant’s intellectual competence in multinational enterprises in Hanoi.